Effect of plant-based functional foods for the protection against salt-induced endothelial dysfunction - Sheung Yin San; Jennifer. M.F. Wan; Jimmy Chun Yu Louie (Food Science and Human Wellness)
ABSTRACT: This study aimed to compare the efficacy of four formulations of plant-based functional foods on the protection against salt-induced endothelial dysfunction. A randomized crossover design was employed. Ten healthy subjects were recruited, and on five separate occasions they received, in random sequence one of the following 5 treatments: 250 mL of plain water (control) alone, and with beetroot powder, celery powder, green tea extract or beetroot powder with green tea extract prior to consuming 150 mL of high-salt chicken broth. Flow-mediated dilation (FMD), blood pressure (BP), heart rate (HR) and pulse-wave velocity (PWV) were measured at fasting and at 30, 60, 90 and 120 min postprandial. Comparing with control, beetroot supplementation led to a significantly increased HR at 30, 60 and 90 min postprandially (P = 0.025, 0.004, < 0.001, respectively). No significant difference was observed for FMD, BP and PWV between control and any of the treatments. Salt reduction may still be the most effective strategy to improve vascular health.